WhatsApp Group Dapat Mempengaruhi Pola Makan Remaja Perempuan Yang Mengalami Gastritis: WhatsApp Groups Can Affect the Diet of Teenage Girls With Gastritis - Desy Vellyasari (Open Access Jakarta Journal of Health Sciences, 2022)
Introduction: Gastritis or ulcer disease is a very disturbing disease. This gastritis usually occurs in people who have irregular eating patterns and eat foods that can stimulate the production of stomach acid. Gastritis is more common in teenagers, especially teenage girls who more often have irregular eating patterns and who like to procrastinate eating. If gastritis is not treated immediately, it will cause dangerous complications such as upper gastrointestinal bleeding, peptic ulcer, and gastric perforation. Objective: The purpose of this study was to determine the effect of WhatsApp groups on the eating patterns of adolescent girls who experience gastritis in Sarua Indah Village, South Tangerang City. Methods: The research design used in this study was the One Group Pre-test Post-test design with the Wilcoxon Signed Rank Test. The sampling technique used purposive sampling with a total sample of 30 respondents. Result: In the Wilcoxon signed rank test results obtained p-value 0.000 <0.05. Conclusion: This study concludes that there is an effect of WhatsApp groups on the eating patterns of teenage girls who experience gastritis in Sarua Indah Village, South Tangerang City in 2021.